Status of Women and Family Planning: The Indian Case - K.E. Vaidyanathan (Asia-Pacific Population Journal, 1989)
The degree of personal autonomy of women in India varies from state to state. Several studies have noted the regional variations in the status of women in India (Karve, 1965; Srinivas, 1978; Mitra, 1979; Dyson and Moore, 1983). Women’s personal autonomy is manifested in practices such as veiling (purdah or ghungat), pressures to get girls married at a very young age (partly to protect their virginity and partly to ensure compliance with parents’ wishes in respect of the choice of spouse), denying or limiting educational or employment opportunities to girls, attaching differential values to sons and daughters, restricting the ability of women to control their fertility by pressuring them to produce children (particularly male heirs), restricting their access to information, and economic and health resources etc.